Problems and ways of increasing the energy efficiency of the sugar factory - Miedviedieva, N. A.; Sukhenko, V.Yu.; Slobodyanyuk, N. M. (НУБіП України, 2019)
Production of sugar and beet requires significant energy consumption Their rational use and the need to preserve the environment is caused not only by the cost of energy resources, but is one of the ways to increase competitiveness. The technology of sugar manufacture at «Novorozhitsky Sugar Plant» is considered, at each stage of technological operations the incoming resources, including material, are determined. The article presents the results of theoretical and practical analysis according to the data of the energy audit of a sugar plant. The results of monitoring the consumption and generation of energy resources for each species were analyzed. The diagnostic survey of the economy allows determining the areas of excessive consumption of energy resources and identifying potential energy conservation specialist. The measures and technical solutions to improve energy efficiency sugar factory are proposed. An economic assessment of the technical solution for the replacement of presses and determine the payback period has been carried out.
Проблеми та шляхи підвищення енергоефективності цукрового заводу
Бурякове і цукрове виробництво потребує значного споживання енергетичних ресурсів. Раціональне їх використання та необхідність збереження навколишнього середовища обумовлено не тільки вартістю енергетичних ресурсів, а є одним із шляхів підвищення конкурентоспроможності. Розглянуто технологію виготовлення цукру на «Новооржицькому цукровому заводі», на кожному етапі технологічних операцій визначені вхідні ресурси, в тому числі і матеріальні. У статті наводяться результати теоретичного та практичного аналізу за даними енергетичного аудиту цукрового заводу. Проведено аналіз результатів моніторингу споживання і вироблення енергетичних ресурсів за кожним видом. Діагностичне обстеження господарства заводу дозволило визначити області надмірного споживання енергетичних ресурсів та визначити потенціал щодо енергозбереження. Запропоновано заходи й технічні рішення щодо підвищення енергоефективності цукрового заводу. Проведена економічна оцінка технічного рішення щодо заміни пресів і визначено термін його окупності.
Keywords: energy audit; sugar production; energy saving; rational consumption; energy efficiency; енергетичний аудит; виробництво цукру; енергозбереження